Peran Orang Tua Dalam Pembelajaran Jarak Jauh (PJJ) pada Pendidikan Anak Usia Dini - Agus Suryana; Siti Herdiana Aulia (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2021)
This study aims to determine what the roles of parents are in accompanying children during the distance learning process during the Covid 19 pandemic at Ciparigi Village, Bogor City. The method used is a case study through online interviews with thematic analysis on 5 parents. The results show that the role of parents is needed in the distance learning process. In general, the role of parents during distance learning, in addition to being a substitute for teachers at home, parents also act as facilitators, motivators, guides for children, and guide children to achieve success of learning in pandemic.